Improving Taxes and Transfers in Australia - Hemmings, Philip (OECD Economics Department Working Papers, 2015)
Getting tax and transfer systems to efficiently deliver sufficient revenues to achieve macroeconomic targets, address goals in re-distribution and social welfare, encourage employment, accommodate business-competitiveness concerns and incorporate environmental issues is difficult. In Australia, slowing economic growth in the wake of the mining boom has sharpened the trade-offs and brought into focus the importance of encouraging broad-based advances in employment and productive capacity while also dealing with other long-term challenges, in particular population ageing and greenhouse-gas emission reduction. This review particularly recommends shifting away from income taxation to indirect taxation, for instance by raising more revenue from the Goods and Services Tax. The report also advises caution in some recent welfare-reform proposals, and advocates broad support for business rather than targeted subsidies and other forms of corporate welfare. As regards environmental policies, the report comments on the proposed Emission Reduction Fund for reducing greenhouse gases and supports reform to vehicle-related taxation. This Working Paper relates to the 2014 OECD Economic Survey of Australia (www.oecd.org/eco/surveys/economic-survey-australia.htm)